Effectiveness of Peer-Supported Practice Strategy in Reducing Public Speaking Anxiety among Students - Maria Theresa Ina Boli Ratumakin (Universitas Pahlawan Tuanku Tambusai, 2026)
Public speaking anxiety remains a major challenge for English as a Foreign Language (EFL) students because it limits their confidence, participation, and speaking performance. Although previous studies have identified the causes of speaking anxiety and highlighted the benefits of peer support, limited research has specifically examined the effectiveness of the Peer-Supported Practice Strategy (PSPS) in reducing public speaking anxiety among senior high school students. Therefore, this study aimed to investigate the effectiveness of PSPS in reducing students’ public speaking anxiety while improving their speaking performance. A quantitative study employing a one-group pre-test–post-test quasi-experimental design was conducted with 15 students. Public speaking anxiety and speaking performance were assessed using a public speaking performance rubric adapted from Brown (2004), which evaluated pronunciation, grammar, vocabulary, fluency, and comprehension, together with an EFL Public Speaking Anxiety Questionnaire administered before and after the intervention. The data were analyzed using descriptive statistics and a paired-samples t-test. The findings showed that students’ mean score increased from 41.73 in the pre-test to 76.27 in the post-test, with a statistically significant difference (p 0.05). These results indicate that PSPS effectively reduces public speaking anxiety while enhancing students’ confidence and overall speaking performance.